A Forensic Linguistic Study - Rio Nur Rachmad; Ahmad Dzo'ul Milal (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2023)
This study discusses the hate speech delivered by Indonesian internet citizens towards Indonesian badminton athletes on social media. This study aims to identify the types of hate speech addressed to Indonesian badminton athletes on the two social media platforms, Instagram and Twitter, and investigate whether the netizens violate the law of hate speech or not. The data are sourced from the official accounts of the Indonesian badminton federation @badminton.ina (Instagram) and @INABadminton (Twitter). The data were collected by documentation technique and then analyzed by using contextual analysis. The result of the study shows that nine comments from eight commenters contain hate speech content including insults, defamation, denigration, unpleasant action, provocation, incitement, and hoax. From the result of the study, it is proved that the commenters violate the Information of Electronic Transactions Law.